Potential Of Natural Destination Or Cultural Heritage Destination? Destination Attributes, Revisit Intention, Perceived Value: Interrelated Impact - Moch. Mahmudi Rosid (Cita konsultindo, 2024)
In tourism destination management, there are several variables that are very important for natural tourism destinations, and are also needed in cultural heritage tourism destinations, in order to create a desire for visitors to make repeat visits in the future. Destination attributes can affect the value perceived by visitors, and then perceived value can affect the desire of visitors to revisit. This research tests a model to explore the existence of natural tourist destinations and cultural heritage tourist destinations for mountain climbing, namely Penanggungan Mountain. Several natural tourist destinations, especially mountain climbing, have developed well, although there are also many competitors that are growing equally of course. The reason for choosing Penanggungan Mountain is because it has the potential to become a more developed tourist destination in the future and can be beneficial for the community around the destination, this potential is related to the potential for natural tourism of course, also the potential for cultural heritage tourism, and Penanggungan Mountain has the potential for both, that's why this research was conducted. After this research is conducted, it is hoped that Penanggungan Mountain can be designated as a world cultural heritage site by UNESCO. This study used a questionnaire distributed to 233 climbers of Mount Penanggungan and the data was processed using SPSS v.24. The results of the hypothesis test show that destination attributes have a significant positive effect on perceived value, and perceived value has a significant positive effect on revisit intention, then destination attributes have a significant positive effect on revisit intention, these three variables are correlated with each other.